Judicial reform index: Bosnia and Herzegovina - (:unkn) unknown (My University, 2016)
The American Bar Association’s Central and East European Law Initiative (ABA/CEELI) developed the Judicial Reform Index (JRI) to assess the process of reforming the judiciaries in emerging democracies. The JRI is based on a series of thirty factors, the assessment of which will enable ABA/CEELI, its funders, and the emerging democracies themselves to better target judicial reform programs and monitor progress towards establishing more accountable, effective, and independent judiciaries.